Income dynamics and health: A test of competing hypotheses. Issue 3 (September 2016) - Liew, Hui-Peng
Abstract: Objective: This study aims to examine the temporal processes underlying the relationship between income and health among the elderly to demonstrate the extent to which income histories have an influence on health changes. Methods: The empirical work of this study will be based on the 1992–2010 Health and Retirement Study (HRS). This study will test the low income hypothesis, the permanent income hypothesis, and the transitory income hypothesis using the method of growth curve modeling. Results: Results from growth curve analyses suggest that distinguishing these three income hypotheses is useful on theoretical, empirical, and policy grounds. It shows that the impact of low income, anticipated fluctuations in household income over the long run, as well as unanticipated income change over the short term on the changes in health over time are shaped along both socioeconomic and racial/ethnic lines. Conclusion: Given the present U.S. circumstances, perhaps something like a national healthcare system like the Obamacare and tax incentives and other benefit systems can be implemented to reduce the existing health disparities. Highlights: Distinguishing these three income hypotheses – the low income hypothesis, permanent income, and transitory income hypotheses is useful on theoretical, empirical, and policy grounds. The impact of low income, anticipated fluctuations in household income over the long run, as well as unanticipated income change over the short term on the changes in health over time are shaped along both socioeconomic and racial/ethnic lines. Education can protect against the detrimental effects against of low income and anticipated long-run fluctuations in income but not unanticipated short-run fluctuations in income. Given the present U.S. circumstances, perhaps something like a national healthcare system like the Obamacare and tax incentives and other benefit systems can be implemented to reduce the existing health disparities.